SAJA‘ IN SURAH AL-‘ĀDIYĀT: A BALĀGHAH ANALYSIS - Fitria, Hanna Sajida; Kamaliah, Nurul (Tanzil: Jurnal Studi Al-Quran, 2025)
Surah Al-‘Ādiyāt, which consists of 11 verses, contains the use of structured, rhythmic, and poetic language styles (saja‘). This study aims to reveal how the rhythm and structure of the language in this surah not only beautify the text but also arouse the emotions and awareness of the readers towards the messages contained in the Qur’an. The problem raised in this study is how the use of saja‘ language style contributes to beautifying and deepening the meaning and message that the Qur’an wants to convey. This research uses a qualitative approach with a content analysis method, with a focus on analyzing the metaphor of the elements used, as well as the uslub (language style) that supports the meaning of the metaphor. The results of the analysis show that there are several types of saja‘ in Surah Al-‘Ādiyāt, namely saja‘ muṭarraf as much as 1 data, saja‘ mutawāzī 3 data, and saja‘ muraṣṣa‘ 1 data. These findings provide a very clear picture of the important role of language styles in enriching meaning and also in increasing aesthetic power in the Qur’an. By using a structured and rhythmic language style, Surah Al-‘Ādiyāt not only succeeds in beautifying the text but also serves as a means to arouse the reader's feelings and understanding of the realities of life, the forces of nature, and the warnings contained in the divine message. This shows how the beauty of the language of the Qur’an helps deepen the spiritual and moral message for humanity.